Auricular reconstruction from rib to 3D printing. Issue 1 (January 2018) - Reighard, Chelsea L; Hollister, Scott J; Zopf, David A
The human ear imparts critical form and function and remains one of the most challenging facial features to reconstruct. Over the past century, surgeons have developed numerous techniques and materials for total auricular reconstruction. Refined costal cartilage techniques have remained the gold standard for the past half-century. Recent advancements with novel materials, tissue engineering and 3D printing provide immense potential; however, prohibitive costs and regulatory steps remain as barriers to clinical translation.